2015
DOI: 10.1021/acsami.5b04724
|View full text |Cite
|
Sign up to set email alerts
|

New Fluorescent Metal-Ion Detection Using a Paper-Based Sensor Strip Containing Tethered Rhodamine Carbon Nanodots

Abstract: A strip of tethered rhodamine carbon nanodots (C-dots) was designed for selective detection of Al(3+) ion using a Förster resonance energy transfer (FRET)-based ratiometric sensing mechanism. The probe consisted of rhodamine B moieties immobilized on the surface of water-soluble C-dots. Upon exposure to Al(3+), the rhodamine moieties showed a much enhanced emission intensity via energy transfer from the C-dots under excitation at their absorption wavelength. The detection mechanism was related to the Al(3+)-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(78 citation statements)
references
References 71 publications
1
77
0
Order By: Relevance
“…For example, Guo et al [244] developed a simple, one-step hydrothermal method for the synthesis of highly fluorescent CNPs with a high quantum yield (68%) and good photo-stability, and can be used to detect Hg 2+ in an aqueous solution. CDs have also been used to detect other ions such as Sn 2+ , Cu 2+ , Ag + , and Al 3+ [245]. …”
Section: Carbon Materials-based Fluorescent Nanoprobes For Sensingmentioning
confidence: 99%
“…For example, Guo et al [244] developed a simple, one-step hydrothermal method for the synthesis of highly fluorescent CNPs with a high quantum yield (68%) and good photo-stability, and can be used to detect Hg 2+ in an aqueous solution. CDs have also been used to detect other ions such as Sn 2+ , Cu 2+ , Ag + , and Al 3+ [245]. …”
Section: Carbon Materials-based Fluorescent Nanoprobes For Sensingmentioning
confidence: 99%
“…Generally, metal‐CDs interactions have been widely implemented in fluorescent‐based sensor applications. For example, FRET‐based fluorescence detection of metal ions such as Al 3+ and K + have been separately accomplished using CDs …”
Section: Introductionmentioning
confidence: 99%
“…For example, FRETbased fluorescenced etectiono fm etal ions such as Al 3 + and K + have been separately accomplished using CDs. [21,22] Copper is an essential element in the human body,p resent in numerousk ey enzymesi ncluding cytochrome co xidase, superoxide dismutase, and tyrosinase. Similart oo ther metal ions, as urplusa mount of copperi nt he body causesr enal disordersa nd damages in the central nervouss ystem.…”
Section: Introductionmentioning
confidence: 99%
“…Although many mPAD applications have emerged over the last decade in elds such as diagnostics, biological samples, food safety, and environmental analysis, [24][25][26][27][28][29][30] mPADs continue to be developed for various aspects of metal detection. Kim et al 31 reported a new uorescent method for Al 3+ and Hg 2+ detection using a paperbased sensor strip containing tethered rhodamine carbon nanodots. The sensor could efficiently detect Al 3+ over other metal ions via forester resonance energy transfer (FRET).…”
Section: Introductionmentioning
confidence: 99%
“…Sensing based on FRET of NCDs is color-tunable and can be identied with the naked eye, providing a new platform for specic metal-ion sensing. Unfortunately, the method still suffers from low sensitivity with limits of detection for Al 3+ 31 and Hg 2+ 32 at around 1 mg L À1 . These levels are insufficient for monitoring aluminum and mercury in drinking water where the maximum allowable aluminum and mercury levels established by the WHO are at 0.1 and 6 mg L À1 , respectively.…”
Section: Introductionmentioning
confidence: 99%